PERAN TUAN SYEKH DALAM MENINGKATKAN PARTISIPASI PEMILIH DI PESANTREN MUSTHAFAWIYAH PURBA BARU KABUPATEN MANDAILING NATAL - Batubara, Faisal; Asrinaldi, Asrinaldi (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
Life in the Pesantren Musthafawiyah Purba Baru is still colored by clientelistic relations, the relationship of interdependence between Tuan Syekh Bakri who acts as a patron and santri as his client. Santri's compliance with Tuan Syekh occurred because there was a Patron-Client relationship between Tuan Syekh and Santri, so that a proper Paternalistic relationship was established. Tuan Sheikh played a pattern of clientelistic relations and also increased participation in choosing santri in order to support the successful implementation of the 2015 Mandailing Natal district election. All the roles played by Tuan Syekh Baksi could increase the participation of santri voters by 71 percent.